The Effect of Nintedanib on T-Cell Activation, Subsets and Functions - Ubieta K; Thomas MJ; Wollin L (Dove Medical Press, 2021)
Kenia Ubieta, Matthew James Thomas, Lutz Wollin Immunology & Respiratory Diseases Research, Boehringer Ingelheim Pharma GmbH & Co. KG, Biberach, GermanyCorrespondence: Lutz WollinBoehringer Ingelheim Pharma GmbH & Co. KG, Birkendorfer Str. 65, Biberach, 88397, GermanyTel +49 7351 54-94993Fax +49 7351 83-94993Email stefan-lutz.wollin@boehringer-ingelheim.comBackground: T cells are important regulators of inflammation and, via release of mediators, can contribute to pulmonary fibrosis. Nintedanib is approved for the treatment of idiopathic pulmonary fibrosis, systemic sclerosis-associated interstitial lung disease (ILD) and chronic fibrosing ILDs with a progressive phenotype. However, how nintedanib targets T cells has not been elucidated.Materials and Methods: We investigated the immunomodulatory effects of nintedanib on T cells and peripheral blood mononuclear cells isolated from healthy donors. Cells were pre-incubated with different concentrations of nintedanib and then stimulated for 24 hours with anti-CD3 with or without anti-CD28 and with or without different cytokines. Levels of interferon gamma (IFN-γ), interleukin (IL)-2, IL-4, IL-5, IL-10, IL-12p70 and IL-13 were quantitated. Western blotting with primary antibodies against phospho-Lck-Y394, phospho-Lck-Y505, Lck-total and Cofilin examined the phosphorylation level of the Lck protein. In vitro T-cell proliferation, T-cell clustering and different T-cell populations were also assessed.Results: Nintedanib blocked T-cell activation through inhibiting Lck-Y394 phosphorylation. Pretreatment of T cells with nintedanib reduced cluster formation as a marker of activation and inhibited the release of IFN-γ, IL-2, IL-4, IL-5, IL-10, IL-12p70 and IL-13 at clinically relevant concentrations ranging from 5– 77 nmol/L. Nintedanib did not alter T-cell proliferation or numbers of CD4+ and CD8+ T cells, but did increase stimulated Th17-like cells without increasing IL-17A levels.Conclusion: These immunomodulatory effects may further explain how nintedanib slows the progression of pulmonary fibrosis in various ILDs.Keywords: cytokines, fibrosis, inflammation, nintedanib, T cells, tyrosine kinase